Mislabeling in seafood products sold on the Italian market: A systematic review and meta-analysis. (March 2023) - Giusti, A.; Malloggi, C.; Tinacci, L.; Nucera, D.; Armani, A.
Abstract: In this study the results of a systematic review and meta-analysis on mislabeling in seafood products sold on the Italian market are presented The aim was especially targeted to answer the research question "What is the mislabeling rate in seafood products sold on the Italian market?". Scientific papers (SPs), were filtered using pre-determined inclusion criteria and data related to sampling and mislabeling was analysed. Samples were categorized according to their taxon (species, family order) or generic market group (MG), market form (unprocessed/processed), distribution channel and geographical area. Samples were considered mislabeled when the species found by molecular analysis did not comply the information indicated in the label. The mislabeling rate (m. r.) was weighted on the sample size and provided overall and for each category. In the 51 selected SPs (published from 2005 to 2022) the most sampled taxa were fish (83.8%): mackerels, cods, herrings, flatfishes and jacks were the most represented. Unprocessed fillet/slice was the most analysed market form (61.4%), and samples were especially collected at retails (76.5%). Ten regions were sampled, especially Tuscany and Apulia. The overall weighted m. r. was 28.4% (CI 26%–30%), falling within the m. r. range found at international level (Luque & Donlan, 2019). M. r. over the CI (>30%) were observed in 1) jellyfishes, European perch, European grouper, Atlantic mackerel and samples labeled as " spinarolo ", " baccalà " or " palombo "; 2) Unprocessed fresh, processed salted and highly processed samples; 3) small distribution channel; 4) Southern regions. Significative differences in m. r. concerned taxa, distribution channels and geographical areas. Despite some bias of the SPs may affect the results (lack of sampling plans; poor data on molluscs and crustaceans; no standardization in m. r. interpretation) this is the first systematic review and meta-analysis that, synthesizing evidence on Italian seafood mislabeling, can support policy making for minimizing frauds impacts.